2015
DOI: 10.3855/jidc.4851
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Blastocystis hominis prevents the development of symptomatic Hashimoto’s thyroiditis: a case report

Abstract: In this case report we describe a 49 year-old man who presented with chronic urticaria, angioedema and soft stool consistency. During diagnostic examinations Hashimoto's thyroiditis was found even though the patient never had clear symptoms of this disease. Blastocystis hominis was isolated through a stool microbiologic examination, implicating that this parasite can cause the development of Hashimoto's thyroiditis and chronic urticaria. After two-weeks treatment with metronidazole the Blastocystis hominis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…13 In 2015, for the first time in the literature a case report was published showing that treatment of BH infection can prevent the development and further stop progression of HT. 14 Our results supported those of the case report, we showed that treatment of BH infection in patients with HT resulted in a significant reduction in TSH and anti-TPO, which subsequently improved HT. Also, serum level of IL-17, a cytokine thought to have a role in HT pathogenesis, was decreased significantly after BH eradication that further supported the improvement of HT following treatment of BH infection.…”
Section: Discussionsupporting
confidence: 92%
“…13 In 2015, for the first time in the literature a case report was published showing that treatment of BH infection can prevent the development and further stop progression of HT. 14 Our results supported those of the case report, we showed that treatment of BH infection in patients with HT resulted in a significant reduction in TSH and anti-TPO, which subsequently improved HT. Also, serum level of IL-17, a cytokine thought to have a role in HT pathogenesis, was decreased significantly after BH eradication that further supported the improvement of HT following treatment of BH infection.…”
Section: Discussionsupporting
confidence: 92%
“…Inicialmente fue considerado un comensal; sin embargo, en las últi-mas décadas hay cada vez más evidencias que sustentan que Blastocystis spp. es patógeno y se asocia a una amplia variedad de trastornos gastrointestinales simples (dolor abdominal, diarrea, flatulencia, vómitos) (2,3) y cuadros más complejos, como anemia ferropéni-ca (2) , urticaria (2,4) , síndrome de intestino irritable (2,5,6) , cáncer colorrectal (7)(8)(9) , artritis reactiva (10) e incluso tiroiditis de Hashimoto (11) . El conocimiento de sus múltiples impactos sobre la salud llevó a que se le preste más atención, por lo que probablemente la prevalencia de blastocistosis se haya incrementado en los últimos años.…”
Section: Introductionunclassified
“…In this study, 57.1% of pre- and perimenopausal women with ST2 suffered from a thyroid disease (Hashimoto’s disease). Rajič et al [ 107 ] provided evidence that the eradication of Blastocystis spp. can prevent the development of both symptomatic Hashimoto’s thyroiditis and chronic urticaria.…”
Section: Discussionmentioning
confidence: 99%